Odpowiedzi

2009-12-13T23:38:36+01:00
Monotoniczność:

-2x+1
f(x)= --------
3x+3

wybieram dowolne x₁ , x₂ ∈ R
zakładam, że x₁<x₂ => x₁-x₂<0
-2x₁+1
f(x₁)=--------
3x₁+3

-2x₂+1
f(x₂)=--------
3x₂+3

-2x₁+1 -2x₂+1 (-2x₁+1)(3x₂+3)-(-2x₂+1)(3x₁+3)
f(x₁)-f(x₂)=-------- - -------- = ------------------------------------- =
3x₁+3 3x₂+3 (3x₁+3)(3x₂+3)

(-6x₁x₂-6x₁+3x₂+3)-(-6x₁x₂-6x₂+3x₁+3)
=--------------------------------------------=
(3x₁+3)(3x₂+3)

-9x₁+9x₂ -9(x₁-x₂)
=----------------- = ----------------- > 0
(3x₁+3)(3x₂+3) (3x₁+3)(3x₂+3)

funkcja jest malejąca

cbdw.